ANTI-INFLAMMATORY ACTIVITY OF EUCALYPTUS SPP. AND PISTASCIA LENTISCUS LEAF EXTRACTS - Qabaha, Khaled; Ras, Sari Abu; Abbadi, Jehad; Al-Rimawi, Fuad (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Eucalyptus spp. and Pistascia lentiscus are among the Palestinian trees that are traditionally used in folkloric medicine in treating many diseases; leaves of which are thought to have anti-inflammatory, antibacterial and antioxidant effects. The goal of this study is to evaluate the in vitro inhibitory effect of Eucalyptus spp. and Pistascia lentiscus extracts on Lipopolysacaride (LPS)-induced Interlukin-6 (Il-6) and Tumor Necrosis Factor-α (TNF-α) by polymorphonuclear Cells (PMNCs). Materials and Methods: Polymorphonuclear cells were isolated from the whole blood using Histopaque (Ficol-1077) method and then cultured in an enriched Roswell Park Memorial Institute (RBMI) medium. Supernatants’ Interlukin-6 (IL-6) and Tumor Necrosis Factor (TNF-α) levels were determined 24 hour after LPS stimulation. HPLC was employed to determine the concentration of phenolic compounds in the extracts. The concentrations of TNF-α and IL-6 were compared using paired-samples t test. Results: Eucalyptus spp. and Pistascia lentiscus leaves extracts have shown significant reduction in the levels of both Il-6 and TNF-α Gallic acid; a strong anti-inflammatory agent was found to be the major phenolic compound in both leaf extracts. However, other antiinflammatory phenolic compounds were detected in Pitascia lentiscus extract including syringic acid and p-coumaric acid, while chlorogenic acid was detected in Eucalyptus spp. leaf extract. Conclusion: Reduction in the levels of Il-6 and TNF-α upon the effect of both Eucalyptus spp. and Pistascia lentiscus extract is an indication of their anti-inflammatory effects. Our results may also indicate that the observed anti-inflammatory effect of the above extracts may be due to the presence of gallic acid and other phenolic compounds.